Co-infections with multiple genotypes of Anaplasma marginale in cattle indicate pathogen diversity - Paidashe Hove; Mamohale E. Chaisi; Kelly A. Brayton; Hamilton Ganesan; Helen N. Catanese; Moses S. Mtshali; Awelani M. Mutshembele; Marinda C. Oosthuizen; Nicola E. Collins (Parasites & Vectors, 2018)
Abstract Background Only a few studies have examined the presence of Anaplasma marginale and Anaplasma centrale in South Africa, and no studies have comprehensively examined these species across the whole country. To undertake this country-wide study we adapted a duplex quantitative real-time PCR (qPCR) assay for use in South Africa but found that one of the genes on which the assay was based was variable. Therefore, we sequenced a variety of field samples and tested the assay on the variants detected. We used the assay to screen 517 cattle samples sourced from all nine provinces of South Africa, and subsequently examined A. marginale positive samples for msp1α genotype to gauge strain diversity. Results Although the A. marginale msp1β gene is variable, the qPCR functions at an acceptable efficiency. The A. centrale groEL gene was not variable within the qPCR assay region. Of the cattle samples screened using the assay, 57% and 17% were found to be positive for A. marginale and A. centrale, respectively. Approximately 15% of the cattle were co-infected. Msp1α genotyping revealed 36 novel repeat sequences. Together with data from previous studies, we analysed the Msp1a repeats from South Africa where a total of 99 repeats have been described that can be attributed to 190 msp1α genotypes. While 22% of these repeats are also found in other countries, only two South African genotypes are also found in other countries; otherwise, the genotypes are unique to South Africa. Conclusions Anaplasma marginale was prevalent in the Western Cape, KwaZulu-Natal and Mpumalanga and absent in the Northern Cape. Anaplasma centrale was prevalent in the Western Cape and KwaZulu-Natal and absent in the Northern Cape and Eastern Cape. None of the cattle in the study were known to be vaccinated with A. centrale, so finding positive cattle indicates that this organism appears to be naturally circulating in cattle. A diverse population of A. marginale strains are found in South Africa, with some msp1α genotypes widely distributed across the country, and others appearing only once in one province. This diversity should be taken into account in future vaccine development studies.